Physical Capacities and Combat Performance Characteristics of Male and Female Olympic Boxers - Hausen, Matheus; Taylor, Lee; Bachini, Flavio; Freire, Raul; Pereira, Glauber; Itaborahy, Alex (Research quarterly for exercise and sport, 2024)
Purpose: The study characterized the anthropometrical and cardiorespiratory profile, and the cardiorespiratory, bio-chemical and immunological responses to 3 × 3 min round (R) free-contact/combat boxing simulation, in elite Olympic Boxers (4 female and 10 male). Methods: The evaluation consisted of resting metabolic rate, anthropometric measurement, maximal graded test exercise (visit 1), free combat simulation (3 × 3 min R, 1 minute rest), and blood samples collected before, during and after the combat (visit 2). Results: Respectively, females and males had (mean±SD; or median: for non-parametric data) body fat percentage (17.2[3.5] and 4.6[0.8]%), predominantly mesomorphic somatotyping, and ${\dot{\rm V}}\rm {{\rm{O}}_{2MAX}}$ V ˙ O 2 MAX (50.0 ± 2.5 and 56.2 ± 5.2 ml.kg −1 .min −1 ). The free combat simulation resulted in high cardiovascular strain [mean heart rate corresponding to R1: 92 ± 3; R2: 94 ± 2; and R3: 95 ± 2% of maximal HR] and blood chemistry indicative of acidosis (following R3: 7.21 ± 0.08 pH, bicarbonate 13.1 ± 3.6 mmol.L −1 , carbon dioxide 13.9 ± 3.8 mmol.L −1 , lactate 15.1 ± 3.8 mmol.L −1, and glucose 8.4 ± 1.3 mmol.L −1 ). Further, notable general catabolism, hematological and immune responses were evident post combat simulation (1-hour post R3: creatinine 95.2 ± 14.5 µmol.L −1 , urea 6.4 ± 1.3 mmol.L −1 , white blood cell accumulation 7.8 ± 2.6 × 10 9 .L −1 , hemoglobin 14.9 ± 0.8 g.dL −1 and hematocrit 43.7 ± 1.9%). Conclusions: Notable cardiovascular strain and acidosis are seen from the 3 × 3 free combat simulation whilst pronounced catabolism and immune responses are evident 1-hour post R3. This characterization is the first in male and female (who recently adopted the 3 × 3 min R format, as used by males) elite Olympic boxers and provides a characterization framework to assist practitioners and athletes in their attempts to deliver evidence-informed practice for specific conditioning session design.